1988
DOI: 10.1111/j.1365-2621.1988.tb07848.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Starch Networks within Rice Flour Noodles and Mungbean Starch Vermicelli

Abstract: Starchy networks within mungbean starch vermicelli and rice flour noodles are characterized by differential scanning calorimetry, X-ray diffraction, mild acid hydrolysis, and gel permeation studies. In these products, native starch structures disappeared but new crystalline organizations were found. An amylopectin-based crystallinity was evident from its B-type diffraction pattern, melting endotherm at 50°C and high susceptibility towards mild acid hydrolysis. In addition, amylose-based structures were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 14 publications
2
80
0
3
Order By: Relevance
“…Lowest CL of 2.0 % was reported for MBS noodles while different sweet potato starch noodles exhibited cooking loss varying from 2.2 to 5.0 % (Chen et al 2003a, b). It was found that SPS noodles made, exclusively from sweet potato starch, with 5 % starch in pregelatinized form (to serve as binder) had only 0.68 % CL, indicating that the heating of starch after extrusion followed by low temperature conditioning accelerated the retrogradation to set the structure of starch noodles as reported for MBS noodles (Mestres et al 1988;Lii and Chang 1981;Singh et al 1989). The noodle making properties of potato, corn and mung bean starches were compared by Kaur et al (2015) who found that the latter had the lowest CL and further reduction in CL was brought about by guar gum fortification, which corroborated with the present findings.…”
Section: Cooking Behaviormentioning
confidence: 94%
See 2 more Smart Citations
“…Lowest CL of 2.0 % was reported for MBS noodles while different sweet potato starch noodles exhibited cooking loss varying from 2.2 to 5.0 % (Chen et al 2003a, b). It was found that SPS noodles made, exclusively from sweet potato starch, with 5 % starch in pregelatinized form (to serve as binder) had only 0.68 % CL, indicating that the heating of starch after extrusion followed by low temperature conditioning accelerated the retrogradation to set the structure of starch noodles as reported for MBS noodles (Mestres et al 1988;Lii and Chang 1981;Singh et al 1989). The noodle making properties of potato, corn and mung bean starches were compared by Kaur et al (2015) who found that the latter had the lowest CL and further reduction in CL was brought about by guar gum fortification, which corroborated with the present findings.…”
Section: Cooking Behaviormentioning
confidence: 94%
“…The cooked noodles were surface dried and weighed to estimate the swelling index (SI). Swelling index (SI) was computed using the formula of Mestres et al (1988) …”
Section: Cooking Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…쌀국수는 대체적으로 인디카 계열의 아밀로오스 함량이 22% 이상인 쌀이 적합한 것으로 알려져 있다 (2). 또한 쌀가루의 수분 흡수력, paste 점성 및 gel의 안정성 등이 쌀가루의 제면성과 관련이 있다 (3)(4)(5). 국내에서도 국수에 적합한 고아미와 같은 쌀 품종을 육종하여 (6), 쌀국수를 생산하기 위한 다양한 연구가 이루어 지고 있다 (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: 서 론unclassified
“…밀의 제과 제빵 적성은 국제적으 로 인증된 표준 방법이 있어서 이에 따른 가공 적성을 시험 할 수 있다 (16,17). 그러나 제면 적성은 아직까지 공인된 실 험 방법이 없으며 특히 쌀을 이용한 제면 적성은 동남아 또 는 중국 등에서 연구 논문 (3,4,18,19) Within a row, p-value: Independent sample t-test. Within a column, values with different letters are significantly different (p<0.05) using Duncan's multiple range test.…”
Section: 서 론unclassified